2019
DOI: 10.1017/s0033291719000898
|View full text |Cite
|
Sign up to set email alerts
|

DSM-5 full syndrome, other specified, and unspecified eating disorders in Australian adolescents: prevalence and clinical significance

Abstract: BackgroundLittle information is available on the prevalence of Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 eating disorders in adolescence, and eating disorders remain unique in the DSM for not systematically including a criterion for clinical significance. This study aimed to provide the first prevalence report of the full suite of DSM-5 eating disorders in adolescence, and to examine the impact of applying a criterion for clinical significance.MethodsIn total, 5191 (participation rate: 70%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 52 publications
7
165
0
2
Order By: Relevance
“…The EveryBODY study is a longitudinal investigation of eating disorders among Australian adolescents. Sampling procedures have been detailed elsewhere [5,14]. In brief, four independent and nine government schools, from a broad range of socioeconomic advantage, participated.…”
Section: Procedures and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EveryBODY study is a longitudinal investigation of eating disorders among Australian adolescents. Sampling procedures have been detailed elsewhere [5,14]. In brief, four independent and nine government schools, from a broad range of socioeconomic advantage, participated.…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…The operationalisation of the eating disorder diagnoses that were assessed in this study has been published previously [5], and an adapted Table of this operationalisation is included in the Supplementary material. Diagnoses assessed included the three major eating disorders (anorexia nervosa, bulimia nervosa, binge eating disorder), the five Other Specified Feeding and Eating Disorders (OSFED; atypical anorexia nervosa, subthreshold bulimia nervosa, subthreshold binge eating disorder, purging disorder, night eating syndrome) and Unspecified Feeding and Eating Disorder (UFED).…”
Section: Eating Disorder Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely posited that adolescence represents a relevant developmental stage during which important changes in social, behavioral, and emotional-motivational functioning occur [12]. For these characteristics, researchers indicate adolescence as a developmental phase at risk for the onset of eating disorders [13,14].…”
Section: Introduction: Eating Disorders In Adolescencementioning
confidence: 99%
“…Eating disorders are complex mental health disorders and have one of the highest mortality and suicide rates of any mental illness [1,2]. Meta-analytical data has shown that the prevalence of disordered eating behaviours are increasing in the general population [3][4][5] and a recent study found the point prevalence of any clinical or subclinical eating disorder to be 22% in Australian adolescents [6]. Another common health problem in adolescence is diabetes, predominantly Type 1 Diabetes (T1D) [7].…”
Section: Introductionmentioning
confidence: 99%